Classical myth & culture in the cinema - Winkler, Martin M. (Oxford : Oxford university press, 2001)
The Katabasis theme in modern cinema / Erling B. Holtsmark -- Verbal Odysseus: narrative strategy in the Odyssey and in The usual suspects / Hanna M. Roisman -- Michael Cacoyannis and Irene Papas on Greek tragedy / Marianne McDonald, Martin M. Winkler -- Eye of the camera, eye of the victim: Iphigenia by Euripides and Cacoyannis -- Iphigenia: a visual essay / Michael Cacoyannis -- Tragic features in John Ford's The searchers / Martin M. Winkler -- An American tragedy: Chinatown / Mary-Kay Gamel -- Tricksters and typists: 9 to 5 as Aristophanic comedy / James R. Brown -- Ancient poetics and Eisenstein's films / J.K. Newman -- Film sense in the Aeneid / Fred Mench -- Peter Greenaway's The cook, the thief, his wife and her lover: a Cockney procne / Janice F. Siegel -- The social ambience of Petronius' Satyricon and Fellini Satyricon / J.P. Sullivan -- Star wars and the Roman empire / Martin M. Winkler -- Teaching classical myth and confronting contemporary myths / Peter W. Rose -- The sounds of cinematic antiquity / Jon Solomon.
Rev. ed. of: Classics and cinema. 1991.
Includes bibliographical references and index.
boek
Keywords: Myth in motion pictures; Mythology in motion pictures; Culture in motion pictures